The People First Network: Radio email for the Solomon Islands - Leeming, David (Technical Centre for Agricultural and Rural Cooperation, 2003)
Imagine the amazement of farmers who are able to receive technical advice on how to deal with a poultry disease. Or of the residents of remote rural villages who can find out about job opportunities and submit their applicat